THE SUCCESS OF THE COMPANY BASED ON THE ACHIEVEMENT OF OBJECTIVES - Guillin Nuñez, Milton; Veloz González, Ángel; Guillin Nuñez, Freddy (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
When the objectives of a company are well defined at least two results will be achieved immediately, as is to be able to imagine what is desired and play a fundamental role in motivation, the objectives of a clearly defined company will make the path easier where do you want to address The Huacho Comercial is a company dedicated to the commercialization of fabrics and textile products, characterized by being one of the sectors with the highest influx of customers in the city, it began with the marketing of shoe products after the shoemaker factories broke down completely, choosing to interfere with other product lines in this case of upholstery and textiles For some years this company has been operating in an empirical way by not having previously established objectives, as a company it is very difficult to go where they want to go. Therefore, the purpose of the present study is to carry out an adequate investigation for this purpose, mention is made of the objectives and their relationship with the company, thus identifying positive and negative aspects which, in large part, help to better decision making.